Fuzzy Foldness of BCI-Commutative Ideals in BCI - Algebras (Global Journal of Science Frontier Research, 2020)
This paper aims to introduce new notions of (fuzzy) n-fold BCI-commutative ideals, and (fuzzy) n-fold weak BCI-commutative ideals in BCI -algebras, and investigate several properties of foldness theory of BCI-commutative ideals in BCI -algebras. Finally, we construct some algorithms for studying the foldness theory of BCI-commutative ideals in BCI -algebras.
Keywords: BCK/BCI algebras; BCI commutative ideals of BCI-algebras